Analisis Keterampilan Teknik Shooting Bola Tangan pada Final Ihf Men’s World Championship 2023 Denmark Melawan Prancis - Anggara Anggara; Achmad Widodo; Afif Rusdiawan; Lutfhi Abdil Khuddus (Mutiara Pendidikan dan Olahraga, 2025)
The goal in playing handball is to put the ball into the opponent's goal as much as possible and concede fewer goals. This study aims to find out how big the success and failure rate of shooting techniques is and what shooting areas or positions are most often used for shooting in the 2023 IHF World Championship final match. This study is a type of quantitative descriptive research, with an approach through match video analysis which is presented in the form of numerical data to find out how big the success and failure rate of shooting is and what shooting techniques are used. The subjects in this study were the Danish and French teams playing in the 2023 IHF World Championship final match. The results showed that the number of successful shots from the Danish team was 34 times while for France it was 29 times with a percentage of 62.96% and 50.87% successful shooting using the jump shoot technique 20 times with a percentage of 65% for Denmark, while for France the flying shoot technique was most often used, namely 22 times and a percentage of 59.09%. The number of shooting failures from the Danish team was 20 times with a percentage of 37.03% while for France it was 28 times with a percentage of 49.12%, shooting failures using the jump shoot technique were 7 times with a percentage of 35% for Denmark, while for France the failure using the flying shoot shooting technique was 9 times with a percentage of 40.90%. The most frequently used shooting area from both teams was the front area, successful shooting for Denmark 18 times with a percentage of 64% and France 18 times with a percentage of 56%, failed shooting from the front area of ​​the Danish team was 10 times with a percentage of 36% while France was 14 times 44%. The results of this study are expected to be used as a reference for players and coaches to develop the right training program in order to improve the effectiveness of shooting techniques to get better results.